Accounting Information Systems as a Strategic Driver of Entrepreneurial Decision-Making in Higher Education - Debi Setiawan; Willy Nofranita; Fitri Yulianis (Suria Academic Press, 2026)
The rapid advancement of digital technology has transformed entrepreneurial activities, requiring university students to possess not only digital literacy but also the ability to utilize information systems to support business decision-making. However, the extent to which E-Commerce knowledge and the use of Accounting Information Systems (AIS) influence entrepreneurial decision-making among accounting students remains inconclusive. This study aimed to examine the effect of E-Commerce knowledge and the use of Accounting Information Systems on entrepreneurial decision-making among Accounting students at Universitas Muhammadiyah Sumatera Barat. A quantitative approach with an associative research design was employed. The study involved 50 accounting students selected using purposive sampling. Data were collected through a five-point Likert scale questionnaire and analyzed using multiple linear regression with IBM SPSS. The findings indicate that E-Commerce knowledge does not significantly affect entrepreneurial decision-making (Sig. = 0.527), whereas the use of Accounting Information Systems has a positive and significant effect (Sig. = 0.027). Simultaneously, both variables significantly influence entrepreneurial decision-making (F = 6.434; Sig. = 0.003), with a coefficient of determination (R²) of 0.215, indicating that the model explains 21.5% of the variance in entrepreneurial decision-making. These findings suggest that Accounting Information Systems play a more strategic role than E-Commerce knowledge in supporting entrepreneurial decision-making among accounting students. Therefore, higher education institutions should strengthen the integration of digital entrepreneurship learning with accounting information systems and financial information management to better prepare students for the digital business environment.